Analisis Efektivitas Pengelolaan Dana Desa Dalam Pemberdayaan Masyarakat: (Studi Kasus di Desa Pasirpanjang Kecamatan Ciracap Kabupaten Sukabumi) - Aldi Febriansyah; Elan Eriswanto; Tina Kartini (AKUNTANSI 45, 2024)
This research aims to assess the effectiveness of village fund management in empowering communities in Pasirpanjang Village, Ciracap District, Sukabumi Regency. The method used is qualitative with a descriptive approach. The research results show that the people in Pasirpanjang Village do not understand the management of their village funds. Village fund management in Pasirpanjang has not been effective because it is not in accordance with Law no. 6 of 2014.